Two inorganic–organic hybrids based on a polyoxometalate: Structures, characterizations, and epoxidation of olefins. Issue 9 (3rd May 2018) - Shi, Zhuolin; Mei, Chongzhen; Niu, Guiqin; Han, Qiuxia
Abstract: Two new inorganic–organic hybrids, [Co3 (bpdo)6 (H2 O)4 Cl2 ][SiW12 O40 ]·H2 O (Co-SiW) and [Ni3 (bpdo)6 (H2 O)4 Cl2 ][SiW12 O40 ]·H2 O (Ni-SiW) (bpdo = 4, 4′-bis(pyridine-N-oxide)), were synthesized from the Keggin-type [SiW12 O40 ] anion and Co(II) and Ni(II) under hydrothermal conditions, respectively, and characterized by elemental analyses, powder XRD, IR spectra, and single-crystal X-ray diffraction. The structural analysis indicates that the 1D chain is constructed from a POM-based half-cage as a secondary building block linked by bridging bpdo ligands. The zigzag chains further stack into a three-dimensional body with channels. The 3D network structure with amphiphilic cavities is shaped by electrostatic interactions through the planes, which has potential to allow molecules such as styrene and H2 O2 ingress and egress. Both of the hybrids demonstrated catalytic activity for epoxidation of olefins, which was examined using styrene and aqueous hydrogen peroxide (30%) as oxidant in acetonitrile, along with Co-SiW and Ni-SiW in a heterogeneous manner at 60 °C. Moreover, the conversion of epoxidation reaction in a heterogeneous manner is close to that of homogeneous catalysis, while being conveniently recovered and steadily reused without change of catalyst structure after epoxidation reactions. Abstract :